Cognitive mechanisms of mindfulness-based pain management in chronic pain - Emily Mohr; Sophie Matthew; Lipika Narisetti; Colin Duff; Poppy Schoenberg (Social Sciences and Humanities Open)
Accruing evidence supports the clinical efficacy of mindfulness treatments in reducing chronic pain symptoms. Although, whether cognitive mechanisms are involved therapeutically for pain amelioration remain unclear. Since aberrations in cognitive executive functioning are apparent in chronic pain and corroborate with higher pain severity and poorer clinical outcomes, we conducted a two-part mechanistic clinical study that aimed to examine; (1) cognitive performance deficits measured during neurophysiology tasks, in chronic pain patients versus healthy controls; and (2) a mechanistic trial into whether Mindfulness-Based Pain Management/MBPM modulates cognitive functioning, and its interplay with clinical symptoms, in chronic pain patients versus a treatment-as-usual/TAU matched patient control. In part 1 (baseline comparison), chronic pain patients and matched healthy controls completed several cognitive neuropsychological tasks and clinical scales. Healthy controls showed better performance on the cognitive tasks involving attention, inhibitory control, and working memory compared to chronic pain patients. In part 2 (clinical mechanistic trial), chronic pain patients underwent MBPM or served as a treatment-as-usual patient/TAU patient control group, and completed testing before and after exposure to MBPM or the TAU period. Results indicated that MBPM had enhancing effects on cognitive performance related to attention, inhibitory control, and psychological well-being. These effects were not seen in the chronic pain TAU matched patient control group. Results also indicated several significant relationships between emotion regulation, pain severity, pain interference, interoception, and cognitive performance. Interoception may play a key role in improving cognitive and emotion processing function in chronic pain patients exposed to mindfulness. Perspective: This article presents new data that mindfulness treatment enhances cognitive and emotion regulation, which appears to interact with interoceptive awareness development, in chronic pain patients. Future research examining mindfulness treatments for chronic pain may benefit from focusing on direct measurements of interoception and emotion regulation and the effects on cognition.